Geschilderd. - Benoot, Kris; Exhibition. Geschilderd. Benoot Gallery Oostende. 2007-01-06. 2007-02-26 (Oostende : Benoot Gallery Oostende, 2007)
Van Anderlecht, Englebert ; Bogart, Bram ; Van den Branden, Guy ; Bronckart, Silvin ; Cortier, Amédée ; Decock, Gilbert ; Delahaut, Jo ; Deprez, Olivier ; Dierickx, Karel ; Van Doorslaer, Etienne (Maur-Etienne) ; Dusepulchre, Francis ; Dypréau, Jean ; de Gottal, Hélène ; Guiette, René ; Jooris, Tom ; Lacasse, Joseph ; Leblanc, Walter ; Leroy, Eugène ; Van Lint, Louis ; Mendelson, Marc ; de Mey, Gaston ; Milo, Jean ; Mortier, Antoine ; Peire, Luc ; Pérez-Flores, Dario ; Raveel, Roger ; Renard, Marc ; Rubens, Albert ; Van Severen, Dan ; Sieverding, Hans ; Swimberghe, Gilbert ; Ubac, Raoul ; Vandercam, Serge ; Verheyen, Jef ; Verstockt, Mark ; Wyckaert, Maurice
Nederlands
boek